KAJIAN SEMIOTIKA PADA INTERIOR GEREJA SANTO YAKOBUS SURABAYA - Sutiono, Rezca Navtalia; ., Sumartono; Santosa, Adi (Dimensi Interior, 2009)
As can be seen from its ornamental elements, the interior of the Santo Yakobus Surabaya Church expressed meaningful signs. These signs serve as a representation of the Catholic liturgy with universal characteristics that become a reference for the Catholic church design in all over the world. This paper aims to reveal the meanings of these signs from the point of view of Peircean semiotics. In this case, these signs are analyzed through the categories of icon, index, and symbol respectively and then combined with the analyses of denotation, connotation and social aspect. The analyses result that the signs in this church convey meanings not only related to the Catholic liturgy but also local and social contexts.